Observing how future primary school teachers reason and generalize: the case of number triangles and Concept Cartoons - Samková, Libuše; Szarková, D.; Letavaj, P.; Tichá, Marie; Richtáriková, D.; Prašílová, M. (Vydavatel'stvo Spektrum STU, 2017)
The contribution focuses on the possibility to use an educational tool called Concept Cartoons as a diagnostic instrument in problem solving and problem posing activities of future primary school teachers. The aim of the presented study is to observe which aspects of future primary school teachers' knowledge related to reasoning and generalization could be investigated through Concept Cartoons that are based on a substantial learning environment called "Number triangles".
Jak budoucí učitelé 1. stupně ZŠ usuzují a zobecňují: případ číselných trojúhelníku a obrázků Concept Cartoons
Keywords: future primary school teachers; reasoning; generalization; Concept Cartoons; substantial learning environment; number triangles; budoucí učitelé 1. stupně ZŠ; usuzování; zobecňování; Concept Cartoons; podnětná výuková prostředí; číselné trojúhelníky